The role of personality traits in development of overtraining syndrome in elite athletes in adolescence: a review study - Hutecková, S.; Bartošová, K.; Frydrychová, Z. (Studia Sportiva, 2017)
Sport performance of elite athletes is accompanied by long-term intensive training. Without adequate period of rest this intensive training can cause overreaching of young athlete. Stress, fatigue, lack of rest and load before and during competitions increase the risk of overtraining that leads to a decrease of performance, persistent fatigue, reduced ability to compete and mood disorders. The main purpose of this study is to map the theoretical background and previous empirical research work to integrate existing knowledge about a role of personality traits in development of overtraining syndrome of young elite athletes and to create basis for a further research in the field of sport psychology. The review of quantitative researches covered the period from 1999 to 2016. Nine relevant studies fulfilling the criteria were chosen. Neuroticism and Conscientiousness were found to be significant predictors of athlete`s performance. The differences between athletes and physically inactive population were found for dimension of Neuroticism, Extraversion and Conscientiousness. Differences between individual and team sports were found in all five dimensions of personality. Some differences occur also in female and male athletes and athletes competing on national and international level of competition compared to those competing on regional level of competition. Due to the symptoms of overtraining syndrome and areas that can be affected by it, it is possible to assume certain changes in personality traits, caused by long-term overload of the athletes. High level of Neuroticism and Conscientiousness are considered as possible risk factors for development of overtraining syndrome.